2005
DOI: 10.1080/01676830590952630
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Periocular Basal Cell Carcinoma Managed by Overnight Paraffin Section

Abstract: For primary BCCs the recurrence rate in this study was low and comparable to that following Mohs' technique. This approach, using routine pathological facilities, therefore offers a viable technique for managing periocular BCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
3
7
1
1
Order By: Relevance
“…In their study Khandwala et al achieved 56.9% histological clearance after the initial operation with 3 mm margins, after re-excision they found tumor cells in 14.3% (5/35) (13). In our study the excision line was 3 mm from the tumor edge and we achieved 62.2% complete primary excision.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In their study Khandwala et al achieved 56.9% histological clearance after the initial operation with 3 mm margins, after re-excision they found tumor cells in 14.3% (5/35) (13). In our study the excision line was 3 mm from the tumor edge and we achieved 62.2% complete primary excision.…”
Section: Discussionsupporting
confidence: 56%
“…Ghauri et al found that 5% of tumors reported as having clear margins on frozen section were seen later to have involved margins on permanent section (8). Khandwala et al, reported the results of using a standard paraffin section technique to confirm histological clearance and found low recurrence rate (1.7%), which is comparable to that following Mohs' technique (13). The principle risk factors for recurrence include previous treatment, localization, large tumor size and an infiltrative or micronodular histological growth pattern (1,18,25).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Mohs micrographic surgery is considered the gold standard, as it is shown to achieve a 98% 5-year cure rate (1773 cases of basal cell carcinoma) 3. Modifications have been sought because of the stringent training and processing requirements of the original technique, and acceptable results have been achieved with staged Slow Mohs4 and multistage fast paraffin sections,5 with maybe a varying of the margins based on tumour morphology 6…”
mentioning
confidence: 99%